An exploratory study on application of various classification models to distinguish switchable-hydrophilicity solvents based on 3D-descriptors. Issue 5 (24th March 2021) - Shiri, Mohammad; Shiri, Fereshteh
ABSTRACT: A set of solvents were classified into the switchable-hydrophilicity solvents (SHSs) and non-switchable-hydrophilicity solvents based on forming or not forming a biphasic mixture with water. SHSs have been developed to make the reaction and product separation processes easier. Herein, three classifier algorithms and various feature selection techniques relay on 3D-molecular descriptors to characterize chemicals and forecast their classes were employed. Cfs-SVM method was employed to perform a classification study. The importance of this study helps to understand more about the presence of hydrophobic groups, their position, and their shape in the molecule.